The new economic geography and regional growth in Brazil and India - Figueirêdo, Lízia de (2002)
This dissertation tries to contribute to empirically assess hypotheses of the "New Economic Geography". Specifically, we tested the relevance of the combination of lower transportation cost with the role of economies of scale in explaining the regional distribution of total activity and of industrial activity. Economies of scale are assumed to be due to "backward and forward" linkages among firms. We also took into account congestion effects and asymmetry among regions.